2011
DOI: 10.1016/j.pdpdt.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the accumulation and dissipation of the photosensitizer protoporphyrin IX during standard dermatological methyl-aminolevulinate photodynamic therapy utilizing non-invasive fluorescence imaging and quantification

Abstract: Background: Dermatological methyl-aminolevulinate photodynamic therapy (MAL-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
4
15
0
Order By: Relevance
“…They used fixed and localized cooling with a temperature drop to 4 °C. A reduced photobleaching and treatment effect was observed of the cooled lesion 27 …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…They used fixed and localized cooling with a temperature drop to 4 °C. A reduced photobleaching and treatment effect was observed of the cooled lesion 27 …”
Section: Discussionmentioning
confidence: 88%
“…A reduced photobleaching and treatment effect was observed of the cooled lesion. 27 In our study, the cooling was applied in a controlled fashion. For standardization during the study, we fixed the arm of the machine so that the air was administrated in a focused area in the centre of the rectangle.…”
Section: Discussionmentioning
confidence: 99%
“…Later optical imaging systems, using liquid nitrogen cooled charge-coupled device (CCD) cameras, managed to circumvent this problem [54]. Recently, Tyrrell et al [55] studied the accumulation and dissipation of PpIX in BCC during MAL-PDT using a commercially available, non-invasive fluorescence imaging system from Dyaderm, Biocam ® . Using this system, they were able to quantify the level of MAL-induced PpIX in BCC tumors at different time points of interest, and concluded that lesions undergoing a second PDT treatment accumulate and dissipate less PpIX than during their first treatment.…”
Section: Detection Of Ppix In the Skin Using Surface Measurementsmentioning
confidence: 99%
“…As reviewed recently (29), several researchers have developed wide-field camera-based imaging (30)(31)(32)(33)(34) and fiber optic probe-based point measurements (35)(36)(37)(38) to investigate the pharmacokinetics of PpIX accumulation in skin tumors (39)(40)(41)(42). Such methods have also been used to evaluate PDT treatment approaches (6,28,43).…”
Section: Discussionmentioning
confidence: 99%